Sustainable Rural Tourism Development in Bandipur, Tanahun District - Dhakal, Bhola Nath (Humanities and Social Sciences Journal, 2021)
Nepal is uniquely endowed with rich and diverse natural and imaginative attraction due to its geographical location and cultural uniqueness in the Himalaya. Tourism is the backbone and leading sector for the development of Nepal. Rural tourism refers to tourists staying in or near rural village, often traditional villages in remote areas, and learning about the village way of life. The main objective of the study was to reveal the challenges that impede sustainable rural tourism development in Bandipur. Household survey with structural questionnaire, FGD, KII and field observation methods were applied for primary data and published/unpublished documents were reviewed and analyzed for secondary data. The findings of the study indicated that there is potential for natural and cultural tourism due to the existence of a variety of related resources in and around the study area. However, raising social awareness, capital investment to maintenance natural and cultural resources, prioritization in infrastructure development and the promotion of local communities’ participation is essential for sustainable tourism development.